An empirical analysis of education expenditure, health care expenditure and economic growth in Malaysia - Wong, Sing Yun; Remali Yusoff (Asian Academy of Applied Business, 2018)
This paper aims to empirically analyze the relationship between the education expenditure, health care expenditure and economic growth in Malaysia over the period of 1980 to 2012. The main interest of this study will be to review and address the mixed results presented by past researches regarding the relationship between education and health care expenditure towards economic growth. The relationship between the variables will be empirically examined for both the short-run and long-run by employing the Johansen Co-integration Technique and Vector Error Correction Model (VECM). The existence of a long run relationship between public education spending, health care expenditure and economic growth was well indicated. It was therefore ascertained that the public spending on education and healthcare sectors are very much a long-run phenomenon as it only generates a return over an extended period of time.